2019
DOI: 10.1111/bjh.16247
|View full text |Cite
|
Sign up to set email alerts
|

GATA2 deficiency and haematopoietic stem cell transplantation: challenges for the clinical practitioner

Abstract: Summary GATA2 deficiency, first described in 2011, is a bone marrow failure disorder resulting in a complex haematological and immunodeficiency syndrome characterised by cytopenias, severe infections, myelodysplasia and leukaemia. The only curative treatment is allogeneic haematopoietic stem cell transplantation (HSCT). Although knowledge on this syndrome has greatly expanded, in clinical practice many challenges remain. In particular, guidelines on optimal donor and stem cell source and conditioning regimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…HSCT was shown to reverse HPV-related lesions as well respiratory problems (PAP) [ 68 , [103] , [104] , [105] ]. Patients with stable disease course, without relevant infections, bone marrow dysplasia and transfusion-dependency might qualify for a watch & wait strategy [ 106 , 107 ]. However, it can be assumed that most GATA2-deficient patients show progressive disease and even with careful watching the best opportunity for low risk HSCT might be missed.…”
Section: Gata2 Deficiencymentioning
confidence: 99%
“…HSCT was shown to reverse HPV-related lesions as well respiratory problems (PAP) [ 68 , [103] , [104] , [105] ]. Patients with stable disease course, without relevant infections, bone marrow dysplasia and transfusion-dependency might qualify for a watch & wait strategy [ 106 , 107 ]. However, it can be assumed that most GATA2-deficient patients show progressive disease and even with careful watching the best opportunity for low risk HSCT might be missed.…”
Section: Gata2 Deficiencymentioning
confidence: 99%
“…In germline GATA2 syndromes, patients with complications of immunodeficiency and/or low-grade MDS, demonstrated improved survival when transplanted at a younger age, with infection and graft-versus-host disease being the major causes of transplant-related mortality. [94][95][96] It has been suggested that the ideal time to proceed to alloSCT in GATA2 disorders is during the hypocellular state, prior to the onset of immunodeficiency, MDS or acquisition of karyotypic abnormalities. 97 Consideration of prophylactic alloSCT in germline CEBPA carriers has been discussed due to the high lifetime risk of AML (>80%) with these lesions.…”
Section: Indications For Allosctmentioning
confidence: 99%
“…Otherwise, patients with GATA2 deficiency present variable grade of immunodeficiency and other comorbidity that could threaten the outcome of HSCT with a high rate of transplant related toxicity. Interestingly, different case series reported thrombotic complications after HSCT in GATA2 deficient patients, sometimes with a fatal outcome [ 36 , 38 , 39 ].…”
Section: Managementmentioning
confidence: 99%